Characterization of fresh cheese produced with milk of different degrees of ethanol stability - PINTO, ANDREA; Goulart , Juliana Querino; Piccinini, Alexandre (Pubvet, 2020)
Unstable non-acid milk (LINA) has instability in the presence of ethanol at 72 ° GL and amounts of lactic acid between 0.14 and 0.18 g / 100mL milk. This milk is discarded by the industry causing economic losses. Aiming to evaluate the possibility of using this raw material, the objective of this work was to evaluate the characteristics of LINA and the yield of unsalted fresh cheese produced from it, comparing it with that produced with normal (LN) and acid milk (LA). For this, 46 milk samples were collected, being 43.47% LN, 32.61% LINA and 23.92% LA. The milks were evaluated for their quality and physicochemical characteristics and cheeses were produced by enzymatic coagulation. Acid milks had lower lactose content, degree of stability, pH and higher freezing temperature when compared to normal milk. LINA, on the other hand, presented ethanol stability lower than LN and equal to LA. The similarity between LINA and LN was also found in lactose, pH and cryoscopy levels. In relation to fresh unsalted cheese produced, it was observed that the fat content and total syneresis were significantly higher when produced with LA. There was no difference between the cheeses produced in yield, dry extract and acidity. Based on the results obtained, it can be stated that, from a compositional point of view, LINA can be used for the production and fresh cheese, since the yield of the cheese produced with it does not present statistical differences in relation to those produced with LN.
Keywords: dairy; abnormal milk; cheese yield